Make A Match Model Assisted by Audio Visual Media on the Motivation and Civics Learning Outcomes - Mufidah; Haryanto; Syarifuddin (Universitas Pendidikan Ganesha, 2023)
The students' motivation in learning Civics (PKn) is still low, and there are many students whose learning outcomes do not exceed the Minimum Mastery Criteria (KKM) set by the school. This research aims to analyze the Make a Match model assisted by audio-visual media in relation to the motivation and learning outcomes of fourth-grade elementary school students. The method used in this research is quasi-experimental with a non-equivalent control group design. The research sample consists of two classes, namely Class IV A and IV B, selected through simple random sampling. Data on learning motivation is collected through a questionnaire, while learning outcomes are measured through multiple-choice and essay tests. The analysis techniques involve both quantitative and qualitative analyses. The results of the research show a significant difference in motivation and learning outcomes between students who learn using the Make a Match model assisted by audio-visual media and those who learn through conventional teaching models. Therefore, it can be concluded that the Make a Match model assisted by audio-visual media has an impact on improving the motivation and learning outcomes of fourth-grade students at UPTD Elementary School in Civics. The implication of this research is that the Make a Match learning model assisted by audio-visual media can facilitate teachers in teaching and depict the learning process realistically, providing a more meaningful learning experience for students.